2019
DOI: 10.1111/trf.15330
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion trends in hip arthroplasty in Korea: a nationwide study by the Korean National Health Insurance Service

Abstract: BACKGROUND Hip arthroplasties are strongly associated with blood transfusion to compensate for perioperative bleeding. The purpose of this study was to evaluate the trends in transfusion associated with hip arthroplasties, using nationwide data supplied by the National Health Insurance Service. STUDY DESIGN AND METHODS We used data from nationwide claims database of the Health Insurance Review Assessment Service. The data managed by the National Health Insurance Service were used to identify 161,934 hip arthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
1
12
1
Order By: Relevance
“…Regarding residential area, an island geography and the lowest number of hospitals and hospital beds per person may explain the highest transfusion rate in liver transplantation in Jeju-do compared to other areas. For kidney transplantation, we found no reason for the higher transfusion rates observed in Busan and Gyeongsangnam-do, but a previous study on hip arthroplasty also showed a higher transfusion rate in these regions [27]. Therefore, further studies are required to reveal the reasons for the higher transfusion rates in relatively simple surgeries such as hip arthroplasty or kidney transplantation in these regions.…”
Section: Discussioncontrasting
confidence: 51%
“…Regarding residential area, an island geography and the lowest number of hospitals and hospital beds per person may explain the highest transfusion rate in liver transplantation in Jeju-do compared to other areas. For kidney transplantation, we found no reason for the higher transfusion rates observed in Busan and Gyeongsangnam-do, but a previous study on hip arthroplasty also showed a higher transfusion rate in these regions [27]. Therefore, further studies are required to reveal the reasons for the higher transfusion rates in relatively simple surgeries such as hip arthroplasty or kidney transplantation in these regions.…”
Section: Discussioncontrasting
confidence: 51%
“…19) Preoperative allogeneic blood transfusions have often been performed to maintain hemoglobin levels before and after fracture operations. 1,20) However, orthopedic surgeons and their patients have been plagued by transfusion in the perioperative period. 2,15,[21][22][23] Hence, surgery without transfusion is of interest, especially for the elderly who often carry multiple comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…4) Therefore, allogeneic blood transfusion is generally required in elderly patients undergoing hip fracture surgery. 1,6) The level of preoperative hemoglobin is a major predictor of the need for transfusion following orthopedic surgery. 2,6) A few studies reported that elective surgery could be done safely in patients with a preoperative hemoglobin level above 10 g/dL if the estimated blood loss was greater than 500 mL.…”
mentioning
confidence: 99%
“… 19 , 20 The lower transfusion rates observed in our cohort likely reflect the implementation of strategies to mitigate perioperative transfusion including preoperative anaemia correction, advances in surgical technique, changes to transfusion thresholds, and the use of tranexamic acid. 7 , 20 , 22 , 28 , 31 , 34 , 41 Using contemporary data, we have reported modern informative estimates of surgery-specific transfusion rates (e.g. hip fracture surgery compared to hip arthroplasty), and of increased transfusion risk for urgent/emergent fracture-related surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…18 Published data describing transfusion practices in orthopaedic surgery are variable. Over the past two decades, the reported frequency of RBC transfusion ranged from 19% to 57% in elective hip and knee arthroplasty, 19 - 26 54% to 83% in revision hip arthroplasties, 27 , 28 and 42% to 56% in hip fracture surgeries. 29 , 30 Previously published studies do not reflect present-day efforts to minimize perioperative transfusion, such as preoperative anaemia correction, modification of surgical techniques, changes to transfusion thresholds, or the use of pharmacological therapies to minimize bleeding, such as tranexamic acid.…”
Section: Introductionmentioning
confidence: 99%